1986
DOI: 10.1104/pp.81.4.965
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Protoheme and Heme a from Glutamate in Maize

Abstract: The heme and chlorophyll precursor Saminolevulinic acid (ALA) can be formed by two biosynthetic routes: from the intact carbon skeleton of glutamate via a five-carbon pathway, which occurs in chloroplasts and bluegreen algae, and by ALA synthase-catalyzed condensation of succinyl-CoA and glycine, which occurs in bacteria and animal mitochondria. The biosynthetic route of plant mitochondrial heme a was determined by incubating terminal epicotyl sections of 8-day-old etiolated Zea mays seedlings in the dark with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Therefore, it was concluded that the protocol used in the present study measures mostly protoheme. However, heme a could not be measured satisfactorily as we did not detect peaks at 429 nm and 588 nm as shown previously (Schneegurt and Beale, 1986).…”
Section: Correlation Of Chlorophyll and Heme Contentmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, it was concluded that the protocol used in the present study measures mostly protoheme. However, heme a could not be measured satisfactorily as we did not detect peaks at 429 nm and 588 nm as shown previously (Schneegurt and Beale, 1986).…”
Section: Correlation Of Chlorophyll and Heme Contentmentioning
confidence: 80%
“…The authentic protoheme when processed similarly also gave two peaks at 418 and 557 nm. Furthermore, it was previously reported that the protoheme purified from the maize seedlings showed two peaks at 418 and 557 nm (Schneegurt and Beale, 1986). Therefore, it was concluded that the protocol used in the present study measures mostly protoheme.…”
Section: Correlation Of Chlorophyll and Heme Contentmentioning
confidence: 82%
“…Protoheme is further used as substrate for heme a and heme c biosynthesis, as well as bilin biosynthesis, by oxidative cleavage. Although the precise subcellular localization of heme a biosynthesis has not been confirmed in plants, it is hypothesized to occur in mitochondria (Schneegurt and Beale 1986). …”
Section: The Heme/bilin Branchmentioning
confidence: 99%
“…ALA is synthesized in chloroplasts from glutamate by the C5 pathway in leaves ( Fig. 1; reviewed by Beale, 1990;Beale and Weinstein, 1991;Jahn et al, 1992), and ALA made in this way is incorporated into hemes as well as Chl (Schneegurt and Beale, 1986). The Cs pathway enzyme GSA aminotransferase has been purified from leaves of barley and pea (Grimm et al, 1989;Pugh et al, 1992), and a cDNA encoding the barley enzyme has been cloned (Grimm, 1990).…”
mentioning
confidence: 99%